(untitled) (Sociologisk Forskning, 2023)
Against a political backdrop where ‘security’ is increasingly associated with crime prevention rather than social security and welfare – and where refugees have come to be seen more as a threat to security than in need of security – this article examines asylum seeking refugees’ sense of security in Sweden. The article is based on an interview study with Syrian asylum-seeking refugees who arrived in Sweden during the ‘refugee crisis’ that culminated in 2015. The refugees’ stories often portrayed Sweden as a safe country, but their own lives were marked by insecurity in relation to — in particular — the asylum process, their economic and housing situation, and their social relations. The article also describes policy changes made before and after the interview study was conducted. These changes are expected to reduce asylum migration, which in turn is expected to reduce crime-related insecurity. At the same time, they lead to increased insecurity for asylum seekers and refugees. The article concludes by questioning whether increasing the insecurity of an already vulnerable group can really make a society more secure.